Estudo comparativo in vitro da resistência ao cisalhamento de discos metálicos de níquel-cromo, com ou sem tratamento de superfície, unidos à dentina bovina com quatro cimentos - Uemura, Eduardo Shigueyuki [UNESP] (1999)
This study was carried out with 80 bovine lower incisors. After extraction and debridement the teeth were cut in two parts (crown and roof), having the pulp tissue removed. Crowns were frozen at -18° C for a maximum period of 28 days and then embedded in type IV stone. Preparations were carried out in superficial dentin (minimum 5mm area) while the remaining dentin thickness was standardized (1.7 to 2mm). 80 Ni-Cr disks (3mm height, 5mm diameter) were submitted to a ceramic firing cycle. Half the disks had a 50µm AL2O3 blast while the other half did not. Cements used were: ZPC -SSW, GICRM Fuji Plus-Fuji; 3M resinous cement - 3M; resinous cement Panavia 21- Kuraray. After ANO VA statistical analysis and Tukey's test (p> 0.05), data showed the following shear bond strength mean values at the interface dentin/cement/Ni-Cr disks: dentin/Panavia 21/ blasted Ni-Cr disks (18,29MPa), dentin/Panavia 21/ non blasted Ni-Cr disks (17, 87MPa); dentin/Fuji Plus/blasted Ni-Cr disks (16,57MPa), dentin/Fuji Plus/non-blasted Ni-Cr disks (16.70MPa); dentin/3M resinous cement/blasted Ni-Cr disks (15.81 MPa), dentin/3M resinous cement/non-blasted Ni-Cr disks (11,40MPa); dentin/ZPC/blasted Ni-Cr disks (3,35 MPa), dentin/ZPC/non-blasted Ni-Cr disks (O,98MPa). Results lead to the conclusions: a) control and tested cements mean shear bond strength values showed a significant statistical difference; b) there was no significant statistical difference between Fuji Plus and Panavia mean shear bond strengths, though both values differed statistically from 3M resinous cement mean shear bond strength; c) blasted and non-blasted specimens mean shear bond strength values showed a statistical significant difference; d) There was no significant statistical difference between resin modified GICRM and Panavia 21 mean shear bond strength values, with or without Ni-Cr disks blasting